2015
DOI: 10.1002/dneu.22303
|View full text |Cite
|
Sign up to set email alerts
|

Activation of brain steroidogenesis and neurogenesis during the gonadal differentiation in protandrous black porgy, Acanthopagrus schlegelii

Abstract: The early brain development, at the time of gonadal differentiation was investigated using a protandrous teleost, black porgy. This natural model of monosex juvenile fish avoids the potential complexity of sexual dimorphism. Brain neurogenesis was evaluated by histological analyses of the diencephalon, at the time of testicular differentiation (in fish between 90 and 150 days after hatching). Increases in the number of both Nissl-stained total brain cells, and Pcna-immunostained proliferative brain cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 75 publications
7
11
0
Order By: Relevance
“…In agreement with previous studies in other teleost species [36][37], a populations of mitotically active cells were found to express the early neuronal marker TUC-4, within Dm, PGZ and VCe M (double-labeled BrdU-TUC-4), or BLBP stem cells (BrdU-BLBP) in PGZ and Dm.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with previous studies in other teleost species [36][37], a populations of mitotically active cells were found to express the early neuronal marker TUC-4, within Dm, PGZ and VCe M (double-labeled BrdU-TUC-4), or BLBP stem cells (BrdU-BLBP) in PGZ and Dm.…”
Section: Discussionsupporting
confidence: 89%
“…To determine the phenotype of proliferating cells double immunofluorescence experiments were performed in adjacent sections, using an early neuronal marker, (Turned On After Division, TOAD, TUC-4) and a glial marker brain lipid binding protein (BLBP) [36][37]. …”
Section: Double Immunofluorescencementioning
confidence: 99%
“…On the contrary, Lin et al . 49 showed that estradiol treatment in the early brain development enhanced cellular proliferation and gene expressions of aromatase and radial glial cell marker ( Blbp ) in black porgy indicating a stimulatory effect of estradiol on the proliferation and development of radial glial cells in the fish brain 49 . Research studies reporting the androgen-induced neurogenesis in vertebrates are much less compared to those that reporting neurogenesis induced by oestrogen.…”
Section: Discussionmentioning
confidence: 99%
“…An anti-proliferative effect of E2 was also seen in adult female zebrafish, where the number of proliferating cells labelled with BrdU decreased in several neurogenic brain regions, including the POA ( 214 ). However, opposite effects were observed in juvenile black porgy treated with E2, where levels of brain aromatase and numbers of proliferative cells increased ( 259 ). A significant reduction in brain cell proliferation was observed after treatment with an aromatase inhibitor, while castration did not affect the number of brain cells.…”
Section: Sex Steroids Mediate Gonadotrope Plasticity Directly and mentioning
confidence: 99%